Dukungan Nenek Berhubungan Erat Dengan Keberhasilan ASI Eksklusif - Eka Oktavianto; Hesti Setyaningrum; Endar Timiyatun (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
Background: Breastfeeding is important in the growth and development of infants. Scope administration Exclusive breastfeeding in the province particularly in Puskesmas Umbulharjo I still low at 45.8%. Support family (grandmother) is one of the most able to give effect to nursing mothers to maximize exclusive breastfeeding.  Objective: To determine the relationship of family support (grandmother) with the success of exclusive breastfeeding in infants aged 6-12 months in Puskesmas Umbulharjo I Yogyakarta.  Methods: The study was adescriptivekorelational. cross sectional The samples in this study usingmethod cluster sampling and obtained the respondent amounted to 147 mothers of infants aged 6-12 months. Data were analyzed using chi square.  Results: The results of this study indicate that there is a relationship between family support (grandmother) with the success of exclusive breastfeeding in infants aged 6-12 months in Puskesmas Umbulharjo I Yogyakarta, based ontest chi square with correlation coefficient 0.601, p value 0.05. The majority support the grandmother in the high category and nursing mothers likely to succeed in exclusive breastfeeding. The higher the grandmother support the more successful in exclusive breastfeeding.  Conclusion: There is a relationship between family support (grandmother) with the success of exclusive breastfeeding in infants aged 6-12 months in Puskesmas Umbulharjo I Yogyakarta.